Efficacy of sclerotherapy with pingyangmycin and polidocanol for venous malformations - He, Guanghui; Zhang, Liping; Guo, Lei; Han, Aiqiang (Frontiers in Surgery, 2025)
ObjectiveTo investigate the treatment outcomes of sclerotherapy with pingyangmycin and polidocanol for venous malformations.MethodsThis retrospective study included patients with venous malformations who underwent sclerotherapy between January 2022 and June 2024. Patient demographics, symptoms, treatment information were gathered from the electronic medical records, and imaging data from the hospital's picture archiving and communication system were reviewed.ResultsA total of 29 patients, composed of 12 males and 17 females, with venous malformations, who underwent 66 procedures during the study period, were analyzed. The lesions were located in the lower limbs in 13 cases, in the upper limbs in 9, in the head and neck in 5, and in the trunk in 2. Twenty-four patients presented with pain, with a median visual analog scale (VAS) score of 4 and the correlation with age was statistically significant. After sclerotherapy, the median VAS score declined to 1, and there was a statistical difference in the overall median VAS score between pre- and post-treatment. According to the evaluation criteria, the treatment response was evaluated as grade 4 in 4 cases, as grade 3 in 17 cases, and as grade 2 in 8 cases; none of the treatment responses was evaluated as grade 1. None of the patients experienced serious adverse reactions.ConclusionSclerotherapy with pingyangmycin and polidocanol is a treatment modality for relieving the clinical symptoms of venous malformations, with good efficacy and few potential risks.